477 VISUALIZATION OF X AND Y CHROMOSOMES OF RABBIT CHONDROCYTES USING FLUORESCENCE IN SITU HYBRIDIZATION. Issue 1 (1st January 2007) - To, N.; Jamali, A.
Abstract : Objective: FISH (fluorescence in situ hybridization) is a valuable cytogenetic testing method that employs fluorophore-labeled DNA probes to identify the presence or absence of specific target genes. The objective of the study is to visualize the X and Y chromosomes of rabbit chondrocytes using FISH. Successful identification of the sex chromosomes will lead to subsequent studies of host and donor cellular interactions in fresh osteochondral allograft transplantations using male and female rabbit models. Methods: FISH were performed on paraffinized tissue sections of Dutch Belt rabbit male femoral trochlea. Slides were treated with Dako antibody, denatured for 2 minutes 30 seconds at 85°C and hybridized overnight with Cambio Y-FitC or X-Cy3 whole chromosome paints. They were then visualized using fluorescence microscopy. Results: Preliminary results indicated slides treated with Y-FitC had ≈30 to 40% of nuclei labeled with strong green signals. Slides treated with X-Cy3 had ≈30 to 40% of nuclei labeled with strong orange signals and increased background. Comparison between Y-Cy3 and Y-FitC probes did not yield any detectable probe binding difference. Conclusion: Our preliminary data suggest that visualization of X and Y chromosomes of rabbit chondrocytes using FISH is achievable and accurate.